Environmental Influences on Pigeonpea-Fusarium udum Interactions and Stability of Genotypes to Fusarium Wilt - Sharma, Mamta; Ghosh, Raju; Telangre, Rameshwar; Rathore, Abhishek; Saifulla, Muhammad; Mahalinga, Dayananda M.; Saxena, Deep R.; Jain, Yogendra K. (Frontiers in Plant Science, 2016)
Fusarium wilt (Fusarium udum Butler) is an important biotic constraint to pigeonpea (Cajanus cajan L.) production worldwide. Breeding for fusarium wilt resistance continues to be an integral part of genetic improvement of pigeonpea. Therefore, the study was aimed to identify and validate resistant genotypes to fusarium wilt and determine the magnitude of genotype × environment (G × E) interactions through multi-environment and multi-year screening. Total 976 genotypes including germplasm and breeding lines were screened against wilt in wilt sick plot at Patancheru, India. Ninety two genotypes found resistant to wilt were tested further for two more years in wilt sick plot at Patancheru and Pigeonpea Wilt Nursery (PWN) comprising of 29 genotypes was constituted. PWN was evaluated at nine locations representing different agro-climatic zones of India for wilt resistance during two crop seasons 2007/08 and 2008/09. Genotypes (G), environment (E) and G × E interactions biplot partitioned main effect into G, E and G × E interactions and significant effects (p≤0.001) were obtained for wilt incidence. Genotype contributed 36.51% of resistance variation followed by environment (29.32%). GGE biplot in integration with boxplot and multiple comparison tests enabled us to identify seven stable genotypes (ICPL 20109, ICPL 20096, ICPL 20115, ICPL 20116, ICPL 20102, ICPL 20106 and ICPL 20094) based on their performance across diverse environments. These genotypes have broad based resistance and can be exploited in pigeonpea breeding program.